The Effectiveness of ACT on Negative Affect, Emotional Processing, and Psychological Hardiness in Women Experiencing Domestic Violence - Borghei , Fatemeh Sadat; Hamvatan, Tahameh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing negative affect, improving emotional processing, and enhancing psychological hardiness in women experiencing domestic violence. Methods and Materials: A randomized controlled trial was conducted with 30 participants, divided equally into intervention and control groups. The intervention group underwent eight 90-minute ACT sessions over eight weeks, while the control group received no treatment. Outcomes were assessed at pre-intervention, post-intervention, and five-month follow-up stages using validated tools for Negative Affect, Emotional Processing, and Psychological Hardiness. Data were analyzed using repeated-measures ANOVA and Bonferroni post-hoc tests, with SPSS-27. Findings: Significant improvements were observed in the intervention group across all variables. For Negative Affect, mean scores decreased from 3.52 (SD = 0.45) at pre-intervention to 2.89 (SD = 0.39) post-intervention and 2.45 (SD = 0.33) at follow-up (F(1,28) = 30.19, p = 0.001, η² = 0.52). Emotional Processing scores increased from 3.20 (SD = 0.40) to 3.80 (SD = 0.37) post-intervention and 4.25 (SD = 0.31) at follow-up (F(1,28) = 34.38, p = 0.001, η² = 0.55). Psychological Hardiness improved from 3.15 (SD = 0.38) to 3.95 (SD = 0.35) post-intervention and 4.10 (SD = 0.32) at follow-up (F(1,28) = 36.57, p = 0.001, η² = 0.58). The control group showed minimal changes across all measures. Conclusion: ACT was highly effective in reducing negative affect, improving emotional processing, and enhancing psychological hardiness in women experiencing domestic violence. The results suggest that ACT is a valuable therapeutic approach for this population, with sustained benefits over time.